2016
DOI: 10.1515/orga-2016-0020
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Study of the Relationship between Entrepreneurial Competences and Innovativeness of Successors in Family SMEs

Abstract: Background and Purpose: In the recent period, scholarly interest for family entrepreneurship and succession has been increasing while the question of innovative capability of family SMEs and of innovativeness of founders and successors is relatively unexplored. Little is known about the factors, which are positively correlated, or affect innovativeness of successors in family SMEs. This research explores the relationship between entrepreneurial competences of the founders in family SMEs and innovativeness of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Furthermore, within this cluster, Letonja et al ( 2016 a) probe the relationship between the entrepreneurial competencies of the founders of family SMEs and the innovation of their successors. The authors convey how the entrepreneurial competencies of founders (their creativity, attitudes towards risk and technical knowledge and abilities) positively correlate with the innovation capacities of their successors.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, within this cluster, Letonja et al ( 2016 a) probe the relationship between the entrepreneurial competencies of the founders of family SMEs and the innovation of their successors. The authors convey how the entrepreneurial competencies of founders (their creativity, attitudes towards risk and technical knowledge and abilities) positively correlate with the innovation capacities of their successors.…”
Section: Resultsmentioning
confidence: 99%
“…IB encompasses three main dimensions: innovation, risk-taking and proactiveness. Innovativeness is the propensity of individuals to create new ideas; risk-taking is defined as the propensity of individuals to take risks with the intention of benefitting the organization, and proactiveness is the anticipation and action taken on future needs, challenges and changes that lead to new opportunities (Letonja et al, 2016;Valsania et al, 2016).…”
Section: Intraprenerushipmentioning
confidence: 99%
“…The evidence compiled over the years suggests that innovation flourishes from the seeds of creativity (Stojcic et al, 2018) and knowledge (Santos-Rodrigues et al, 2010) and is found within and outside (Brink, 2017;Tobiassen and Pettersen, 2018) of organizations. Among the internal drivers of innovation, considerable attention has been paid to knowledge (Radas and Božić, 2009), business intelligence (Huges, 2009;Mohsin et al, 2015;Agostino et al, 2013;Ali et al, 2017) and the personal values of staff and managers (Potocan and Nedelko, 2013;Letonja et al, 2016).…”
Section: Introductionmentioning
confidence: 99%